Online Travel Agencies (OTAs) and Hoteliers’ Relationships: Do Social and Cognitive Relationships Matter? - Wisker, Zazli Lily (ASEAN Journal on Hospitality and Tourism, 2022)
This study aims to discover if social relationship as measured by shared value, duration and non-economic satisfaction and cognitive relationship as measured by task performance and economic satisfaction affect OTAs-hoteliers’ relationship, which is measured through trust and commitment. Data was collected from hotels’ operation managers, senior managers, financial executives, business owners, and partners through online surveys. A total of 208 usable questionnaires were returned from 577, resulting in a response rate of 36.04 per cent. The hypotheses were tested using SEM and mediation effects were tested and translated using Hair et al. (2014) nested structural model concept. The results indicate partial mediation for cognitive domain - relationship commitment and full mediation for social domain - relationship commitment affects. Trust forms as the mediating variable.